The role of livelihood assets in affecting community adaptive capacity in facing shocks in Karangrejo Village, Indonesia - Gunawan Prayitno; Aidha Auliah; Achmad Efendi; Ainul Hayat; Aris Subagiyo; Aulia Putri Salsabila (Economies, 2025)
This study addresses a theoretical gap by examining how multiple livelihood assets collectively enhance rural communities' adaptive capacity and contribute to rural resilience theory. Using structural equation modeling, data were collected from June to August 2024 from 372 randomly selected households in Karangrejo Village, Indonesia, to test whether livelihood assets significantly influence adaptive capacity in response to diverse economic, social, and environmental shocks. The findings reveal that human, natural, physical, and social capital show a strong, positive effect on adaptive capacity, whereas financial capital alone does not significantly enhance resilience. Despite the limited geographic scope, the results underscore that comprehensive asset combinations - rather than reliance on a single form of capital - strengthen a community's capacity to withstand shocks. This integrated perspective suggests that balanced investments across multiple forms of capital foster sustainable and flexible adaptation strategies, enabling communities to navigate uncertainty and maintain stability. The study highlights the critical importance of diversifying livelihood assets to foster long-term rural resilience and improve quality of life, offering practical insights for policymakers, practitioners, and researchers in developing holistic interventions that support adaptive capacity.
Keywords: 330; adaptive capacity; livelihood assets; rural resilience; Karangrejo Village; Indonesia; shocks; structural equation models